Hurtownie danych narzędziem wspomagającym procesy decyzyjne w zarządzaniu: Data warehousing tool for decision – making in management - Kopczewski, Marian (Management and Administration Journal, 2021)
Every decision maker should remember that the perfect hardware is only potential, which can be used only after the relevant systems. Often we do not realize that the computer is so good, how good is its software, which unfortunately we forget introducing management information systems, including a variety of decision-making, in all kinds of organizations. It can therefore be concluded that the computer is only as good as its software is good, allowing to gather, define, archiving, analysis and distribution of key information reliable decision-making. Dynamically developing organizations (already possessing information systems) in order to enter the next level of management, reduce costs, operate more efficiently, and especially to make rational decisions benefit from data warehouses.